Effect of Photoperiod on Haematological Parameters of Surti Does and Kids - Padheriya, Yogesh D.; Singh, Rana Ranjeet; Chaudhary, Sandhya S.; Patel, Navin B. (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Effect of artificial long-day photoperiod under tropical climate was limited and no such reports were available for Surti goats and  kids. Therefore, the present study was undertaken to know the effect of photoperiod on monthly haematological parameters of 24  parturient does and their kids for 5 months. The animals were divided into four groups after their parturition/ birth and were subjected  to photoperiodic treatment. Control (n=6 does and kids, natural photoperiod, 11.5 h light : 12.5 h darkness) group, T1 (n=6 does and  kids, 14 h light : 10 h darkness) group, T2 (n=6 does and kids, 16 h light : 08 h darkness) group and T3 (n=6 does and kids, 08 h light :  16 h darkness) group. Blood samples were collected at monthly interval during entire experimental period. Positive effect of long-day  photoperiod treatment was observed on haemoglobin and total erythrocyte count. However, the PCV % and total leukocyte count was  significantly higher in short day photoperiod.
Keywords: Haematological parameter; Photoperiod; Surti doe; kid